Gambaran Tingkat Stres Pelajar SMP Terkait Sistem Pembelajaran Online - Gusrina Komara Putri; Ikhfa Amelia (Indonesian Journal of Nursing Scientific, 2021)
Overview of the Stress Level of Middle School Students Related to Online Learning System at SMPN 1 Karang Bahagia, Bekasi Regency. Background: The stress felt by students because of the change in the learning system from face-to-face to online learning is influenced by the pressures that occur within students. Academic demands that must be completed by students in a short time make students experience stress in the learning process. Objective: This study aims to describe the characteristics of stress levels in students of SMPN 1 Karang Bahagia, Bekasi Regency. This study uses a quantitative descriptive design with a sampling technique using purposive sampling, a sample of 110 students. The instrument used is the Perceived Stress Scale, the analysis used by univariate analysis. Results: The description of the stress level of junior high school students related to online learning methods at SMPN 1 Karang Bahagia Bekasi Regency shows moderate stress (56.4%). Conclusion: In this study, students experienced more moderate stress, the stress that occurred was caused by pressure and demands from the teacher.